Metal Complexes of Singly, Doubly and Triply Linked Porphyrins and Corroles: An Insight into the Physicochemical Properties. Issue 24 (7th March 2022) - Hazari, Arijit Singha; Chandra, Shubhadeep; Kar, Sanjib; Sarkar, Biprajit
Abstract: Metal complexes of multi‐porphyrins and multi‐corroles are unique systems that display a host of extremely interesting properties. Availability of free meso and β positions allow formation of different types of directly linked bis‐porphyrins giving rise to intriguing optical and electronic properties. While the fields of metalloporphyrin and corroles monomer have seen exponential growth in the last decades, the chemistry of metal complexes of bis‐porphyrins and bis‐corroles remain rather underexplored. Therefore, the impact of covalent linkages on the optical, electronic, (spectro)electrochemical, magnetic and electrocatalytic activities of metal complexes of bis‐porphyrins and ‐corroles has been summarized in this review article. This article shows that despite the (still) somewhat difficult synthetic access to these molecules, their extremely exciting properties do make a strong case for pursuing research on these classes of compounds. Abstract : Metal complexes of directly linked metalloporphyrine and corrole oligomers have been extensively studied due to their intriguing optical and electronic properties. In this regard, the impact of the different type of direct linkages on electrochemical, magnetic, electronic and electrocatalytic properties of various metallopophyrine and corrole oligomers have been discussed at length in this Review article.